Optimalisasi Pengelolaan Prinsip Keuangan BUMDes: Upaya Mewujudkan Pembangunan Desa yang Berkelanjutan - didha putri; Mahirun; Anggrainy Putri Ayuningrum (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Abstract.One of the factors that determine village independence is being able to generatePADes. PADes is income from optimizing village potential. Referring to Law no.6 of 2016 concerning Villages, article 72 paragraph (1) explains that villageoriginal income can come from business results, asset results, self-help andparticipation, mutual cooperation, and other village-original income. This studyform of finding the problem that BUMDes is not yet optimal inSumurjombalongbogo Village, Pekelongan Regency in supporting theacquisition of PADes. This study aims to identify and analyze the managementprinciples of BUMDes in Sumurjomblangbogo Village in accordance with theDevelopment System Dynamics Study Center and to identify and analyze thefinancial statements of BUMDes in Sumurjombangbogo. This research usesqualitative and quantitative descriptive analysis to obtain answers according tothe objectives set. The results of this study are that the SumurjomblangbogoBUMDes have implemented the principles of good financial management and inthe coming year will realize business expansion in various business fields.